Mycobacterium microti Infection in Wild Boar (Sus scrofa): Histopathology Analysis Suggests Containment of the Infection - Pigoli, Claudio; Tranquillo, Vito; Gibelli, Lucia Rita; Gaffuri, Alessandra; Alborali, Giovanni Loris; Pacciarini, Maria; Zanoni, Mariagrazia; Boniotti, Maria Beatrice; Sironi, Giuseppe; Caniatti, Mario; Grieco, Valeria (Frontiers in Veterinary Science, 2021)
The European wild boar [WB] (Sus scrofa) population has rapidly expanded over the years, raising public health concerns over the species reservoir of several pathogens, including Mycobacterium microti (Mm), a Mycobacterium tuberculosis complex member. In this study, we aimed to investigate the natural infection Mm in WB by statistically evaluating the granulomatous lesions' histological features and Mm microbiological isolation. We analyzed 103 WB retropharyngeal and submandibular lymph nodes (LNs) for Mm identified by gyrB PCR-restriction fragment length polymorphism, and were retrospectively selected and histologically assessed. For each sample, Hematoxylin-eosin and Ziehl–Neelsen stained slides were evaluated. Considered histological variables were: the number of granulomas, size and maturational stage of granulomas, granulomas completeness within the section, number of multinucleated giant macrophages (MGMs), and acid-fast (AF) bacilli per granuloma. Furthermore, Mm microbiological results were also considered. Investigated parameters were statistically analyzed. Mm microbiological isolation was negatively influenced by granulomas maturation and positively affected by AF bacilli's presence within the section. Granuloma maturation was positively influenced by granuloma size and granuloma incompleteness and negatively affected by the number of granulomas in the section and the number of MGMs within the granuloma. The obtained results indicate that granulomas' maturation ensured an efficient containment of Mm infection in the WB, making the intraspecific transmission of the disease an unlikely event.